Impact of Flood on Dynamics of Mimosa pigra Populations in Affected Kelantan River Basin (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
Kelantan is one of the east coast states of Malaysia, which has faced yearly flooding catastrophe especially during north-east-monsoon season. Most of the land use from upstream to downstream of Kelantan River Basin was affected after December 2014 when the worst flood was recorded for decades. Due to the immense flood, Mimosa pigra is spreading forming dense thickets belt along the riparian vegetation area. It has transformed the river water regime. M. pigra is identified as the worst invasive species in Malaysia and caused massive threat to riverine ecosystem. It’s considered to be a colonizer of mainly wetland and seasonally flooded areas. The dispersal process by which this rapid colonization was achieved has yet to be fully documented. The study was done in three sampling areas along Kelantan river basin (upstream, downstream, outfall) focusing on the distribution of M. pigra after the recent flood. Based on Landsat TM image classification analysis and ground thruting, result showed 60% (upstream), 40% (downstream) and 70% (outfall) of accuracy assessment respectively. For each of the 30 sampled point (a 7.5m radius circle), M. pigra has covered an average of 23.04% of the area with a total of 2,309.58 m2/ha.
Keywords: flood; kelantan river basin; Mimosa pigra